Unusual Case of Large Conglomerate Mass in Abdomen (Global Journal of Medical Research, 2024)
Testicular seminoma commonly occurs in young men aged between 15 and 45 years old Those with testicular cancer may present with a lump or swelling in the testicle If treated and managed early patients can expect a greater than 90 success rate However advanced stages of testicular seminoma can lead to eventual metastasis We present a 45-year-old male patient with a prior history of testicular seminoma who was admitted to the emergency department with abdominal distension and mild abdominal pain The CT identified a rather sizable abdominal mass and the biopsy report confirmed metastatic testicular seminoma This patient is currently on active chemotherapy with bleomycin cisplatin and etoposide
Keywords: metastatic testicular seminoma; abdominal pain; abdominal distention